Revitalisasi Industri Keripik Berbasis Digital Untuk Mengoptimalkan Perekonomian Masyarakat - Zulkifli Sultan; Abdul Rahman Rahim; Muhammad Sulaiman (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This activity aims to improve the capabilities of business partners in digital marketing and banana chips production. Bearing in mind that currently, South Sulawesi Province is the largest banana producing region, with this opportunity we can utilize bananas to become a popular product for the community by providing value. One of the values is making banana chips that have various flavors, especially since banana chips can be consumed by young and old age segments. The method used in this service is a needs analysis process, mentoring which also educates partners, and evaluation through distributing questionnaires and interviews. The results of this service were able to increase sales and maximize the digital business marketing process. The presence of the Open University PKM team provided a lot of experience so that partner sales increased significantly, and digital marketing was carried out to inform about uchips banana chips products. Apart from that, partner sales increase the community's economy by opening up job opportunities